Real empowerment or mere political rhetoric: a formative evaluation of the youth empowerment facilities in Gweru district, Zimbabwe, - Maraire, Fungayi Promote (Midlands State University, 2014)
Zimbabwe embarked on a youth empowerment drive in 2009 through the setting up of Youth Empowerment Facilities. The Youth Empowerment Facilities are a partnership between the Government of Zimbabwe through the Ministry of Youth Indigenisation and Empowerment and various financial institutions that include CBZ Bank, Central African Building Society and Stanbic Bank. The Youth Empowerment Facilities are a micro credit scheme whose broad objective is to alleviate poverty amongst the youths in Zimbabwe through funding of income generating projects started by youths. It was hoped that the funded projects would result in employment creation and that technical entrepreneurial skills would be imparted to the youth through the programme. The study was a formative evaluation of the Youth Empowerment Facilities in Gweru District (Zimbabwe) which sought to determine how the programme was being implemented and the progress or lack of towards the achievement of the programme’s goals. The research established that some of the objectives of the programme were indeed relevant to the current challenges being faced by the youth in Zimbabwe. It was however suggested that other dimensions of empowerment such as the political and social empowerment be included in order for real youth empowerment to be achieved. The study noted that the implementation process was being hampered by inadequate funding, abuse of funds, non repayment of loans, high failure rate of the youth projects funded and the high rate of rejection of the youths’ project proposals by the financial institutions. There were however a few success stories noted by the study. In terms of progress made in achieving the objectives, the study noted that very little progress had been made so far. This was because very few youth projects had been funded as compared to the number of youths in the district that were in need of funding. The high rate of collapse of the youth projects funded coupled with the failure to sustain production levels achieved after accessing the loans have meant that chances of employment creation have been limited. The programme has so far had very little effect on youth poverty and unemployment in Gweru Urban District which remains high.